A review: The Role of Warehouse Laboratory for Higher Education - Hizba Muhammad Sadida; Pebi Yuda Pratama; Hanissa Okitasari (Universitas Pendidikan Indonesia, 2022)
An unwell-prepared graduate from logistic education is being a key issue which has been being discussed by government, practitioners, education institutions and economic units as well as who will get benefits of this education by the possibility of obtaining a competent graduate. Warehouse laboratory is the solution for fulfilling the gap where competencies could be developed which is required by industry. This paper aims to explain the process of implementation and utilization of warehouse laboratory at the higher education Introduction. Hence, warehouse laboratory has a pivotal role in the development logistics education that is not only for education and research but also for preparing graduate students to be a competent workforce which is required by industry.